Listening Anxiety Among EFL Tadulako University Students: Causes And Coping Strategies From Students’ Perspectives - Muhammad Irli Ma'arif; Aminah Suriaman; Maf’ulah Maf’ulah; Muhammad Arid (MASI Mandiri Edukasi, 2026)
Listening anxiety is a common affective factor that can hinder English as a Foreign Language (EFL) learners’ listening comprehension and academic performance. Therefore, this study aimed to investigate the causes of listening anxiety and the coping strategies employed by EFL students at Tadulako University from students’ perspectives. This research employed a qualitative descriptive approach, with data collected through semi-structured interviews involving EFL students. The findings revealed that the majority of participants (90.51%) experienced low levels of listening anxiety, while a smaller proportion reported moderate (7.66%) and high (1.83%) levels of anxiety, which significantly affected their academic performance. The main sources of listening anxiety included fear of misunderstanding spoken English, fear of negative evaluation by peers and instructors, and limited vocabulary knowledge. To cope with listening anxiety, students employed various strategies, including cognitive strategies (note-taking and inferencing), metacognitive strategies (pre-listening preparation and self-evaluation), and affective strategies (such as deep breathing exercises). The study concludes that listening anxiety among EFL learners is influenced by both cognitive and affective factors, highlighting the importance of incorporating students’ coping strategies into listening instruction. These findings suggest that EFL instructors should integrate anxiety-reduction techniques and strategy-based instruction into the curriculum to create a more supportive learning environment and enhance students’ listening skills and overall language proficiency.